An influence of the SS316L powder particle shape to the densification of metal injection moulding (MIM) compact - Jamaluddin, Khairur Rijal (Penerbit UTM, 2008)
Metal injection molding (MIM) has acquired increasing importance as a production technique for small, complex stainless steel components [1, 2]. Sintering is critical for determining the final quality of the parts produced by MIM. Because high sintered density is imperative for good mechanical properties and corrosion resistance, achieving full or near-full density has been a major objective of sintering [3]. Therefore, most research on 316L stainless steel sintering to date has focused on the sintering behavior of the molded parts especially for gas-atomised powder in argon environment [3-6]. An understanding of the factors influencing densification of stainless steels is important as over 50% of the injection molded and sintered components are made from stainless steel compositions [7]. In a metal injection molding (MIM) process, gas-atomised powder is generally used due to their high packing density and associated feedstock rheology. The sintered components exhibit mechanical and corrosion properties similar or superior to that of wrought material. Water-atomised powders in MIM can be economical and have an improvement in shape retention during debinding and sintering. However, their use comes with a penalty of lower powder loading and sintered density, with a corresponding degradation in the mechanical and corrosion properties. Studies reveal that injection molded and sintered components using water-atomised 316L stainless steel powders have a residual porosity of 3–5% for similar particle characteristics and sintering conditions as that of gas-atomised powders [5]. This article investigates a densification of SS316L gas and wateratomised compact sintered in high vacuum environment at temperature ranging from 1340 to 1400 °C.